The significance of consciousness - Siewert, Charles P., 1959- (Princeton University Press, 1998)
Charles Siewert presents a distinctive approach to consciousness that emphasizes our first-person knowledge of experience and argues that we should grant consciousness, understood in this way, a central place in our conception of mind and intentionality. Written in an engaging manner that makes its recently controversial topic accessible to the thoughtful general reader, this book challenges theories that equate consciousness with a functional role or with the mere availability of sensory information to cognitive capacities.